Implementasi Kebijakan Kementerian Agama Terhadap Moderasi Beragama di Provinsi Kepulauan Riau - Krismon Tri Damayanti; Khatijah ijah; Halimah Halimah; Utha Chuandra utha; Hanafi Hanafi; Yusuf Hadamean Usuf (JAKA: Jurnal Analisis Kebijakan Kementerian Agama, 2023)
Religious moderation is one of the efforts to strengthen and strengthen a harmonious, safe, and peaceful religious life. The government in this case the Ministry of Religious Affairs considers strengthening religious moderation as a strategic effort in maintaining the integrity of the nation amidst the religious diversity in Indonesia. The study in this paper is one of the efforts to see the extent to which the Ministry of Religious Affairs' policy on religious moderation programs is implemented in the people of Riau Islands Province. In this study, researchers used interview and observation techniques at the Regional Office of the Ministry of Religious Affairs of Riau Islands Province. The results of research related to the Ministry of Religious Affairs' policy towards religious moderation in the Riau Islands province are that religious moderation has been implemented in the Riau Islands province with programs and activities carried out. Religious moderation activities are carried out by socializing continuously through Banners, Banners, Flayers, and social media (Whatsapp, Facebook, Instagram, Youtobe, and Tiktok), as well as strengthening religious moderation is intensified by coaching extension workers, teachers, students and the community.